Worldwide barriers to genetic testing for movement disorders - Gatto, Emilia M.; Walker, Ruth H.; Gonzalez, Claudio; Cesarini, Martin; Cossu, Giovanni; Stephen, Christopher D.; Balint, Bettina; Rodríguez‐Violante, Mayela; Jankovic, Joseph; Morgante, Francesca; Jinnah, Hyder A.; Albanese, Alberto; et al. (European journal of neurology, 2021)
Background and purpose Despite enormous advances in identifying genetic variants responsible for many neurological diseases, access to genetic testing may be limited in clinical practice. The objective of this study was to assess worldwide access to genetic tests for movement disorders and factors impacting their utilization. Methods The Rare Movement Disorders Study Group of the International Parkinson and Movement Disorder Society designed an online survey electronically mailed to all 7815 members. Results Survey data completed by 1269 participants from 109 countries were analysed. Limited access to geneticists and genetic counsellors was reported in many world regions compared to Europe and North America. Availability of genetic testing was limited, with rates of access lower than 50%. Genetic testing for chorea was the most commonly available. For parkinsonism, dystonia, ataxia, hereditary spastic paraplegias and metabolic disorders, there was limited access to genetic testing in all countries compared to Europe and North America, with significant differences found for Africa, Central/South America, Asia. In many regions, genetic testing was supported by either private or public funding. Genetic testing was free of charge in Europe according to 63.5% of respondents. In North America, Africa, Central/South America, Asia and the Middle East access to free of charge genetic testing was by far significantly lower compared to Europe. Conclusions This survey highlights difficulties in accessing genetic testing and individuals with expertise in genetics at the worldwide level. In addition, major disparities in genetic testing amongst world regions are highlighted, probably due to a variety of factors including financial barriers. In this online survey designed by the Rare Movement Disorders Study Group of the International Parkinson and Movement Disorder Society, worldwide access to genetic tests for movement disorders and factors impacting their utilization were investigated. Access to geneticists and genetic counsellors as well as to genetic testing for movement disorders was limited at worldwide level, with significant differences in most world regions compared to Europe and North America. Our results highlight major disparities in accessing genetic testing and experts in genetics amongst world regions, probably due to a variety of factors including financial barriers.